Pengembangan Pembelajaran Kebugaran Jasmani Unsur Kelincahan Berbasis Multimedia Interaktif - Arief, Muhammad Ghazali; Kurniawan, Ari Wibowo; Kurniawan, Rama (Sport Science and Health, 2021)
Abstract: This development research aims to develop learning of physical fitness agility elements based on interactive multimedia in SMP Negeri 4 Malang. Using the Research and Development (R&D) model with Lee & Owen. Using a small group trial subject of 20 students and a large group trial subject of 60 students consisting of class VII and class VIII. Based on the results of data analysis obtained from learning experts with a percentage of 93%, physical fitness experts with a percentage of 91%, media experts with a percentage of 90%, small group trials 89%, and large group trials 89%. Based on the analysis of the data that has been obtained, it is concluded that the development product is suitable for use in the learning process.Â Abstrak: Penelitian pengembangan ini bertujuan mengembangkan pembelajaran kebugaran jasmani unsur kelincahan berbasis multimedia interaktif di SMP Negeri 4 Malang. Menggunakan model Reseach and Development (R&D) dengan Lee & Owen. Menggunakan subjek uji coba kelompok kecil 20 siswa dan subjek uji coba kelompok besar 60 siswa terdiri dari kelas VII dan kelas VIII. Berdasarkan hasil analisis data yang diperoleh dari ahli pembelajaran dengan persentase 93%, ahli kebugaran jasmani dengan persentase 91%, ahli media dengan persentase 90%, uji coba kelompok kecil 89%, dan uji coba kelompok besar 89%. Berdasarkan analisis data yang telah diperoleh, disimpulkan bahwa produk pengembangan layak digunakan dalam proses pembelajaran.